Vaccination in a Post-truth World: The Role of Self-rated Health, (Mis)trust, and Intuition - Katelin Albert; Garry Gray (SAGE Open)
This article offers a qualitative analysis of how people discursively justify and make sense of their COVID-19 vaccination intentions. Drawing on in-depth interviews with 39 people in British Columbia, Canada, just prior to the availability of a COVID-19 vaccine (Oct–Dec 2020), the objective of this study is to explore why some citizens are in favor of a COVID-19 vaccination while others are against receiving a COVID-19 vaccine. Our qualitative data reveals three key factors that inform people’s discursive justifications of their COVID-19 vaccine intention: (i) self-rated health, (ii) (mis)trust, and (iii) intuition. First, we found that vaccination justification was coordinated through participants’ self-rated views of their own health and whether they adopted an individualist or a collectivist cultural perspective of risk. Second, participants’ justification was tied to (mis)trust in government and public health initiatives, affecting participants’ upcoming willingness to receive a COVID-19 vaccination. And third, drawing on the concept of epistemic repertoires, we observed that vaccination justification was expressed through various types of intuitions that were grounded in personal “gut feelings,” religious beliefs, and scientific reasoning. Overall, our research highlights the importance of qualitatively examining the cultural and social meanings that citizens attach to vaccines and the “cultural scripts” they draw on when responding to public health vaccination initiatives. Our findings reveal the need for local, contextualized, and community generated health strategies that go beyond simply providing public health information.